Childhood socioeconomic status and social integration in later life: Results of the Japan Gerontological Evaluation Study - Toyo Ashida; Takeo Fujiwara; Katsunori Kondo (Elsevier, 2022)
Older people's social integration is important for their health and well-being. However, few studies have investigated the determinants of older adults' social integration through childhood socioeconomic status (SES). This study investigated the association between childhood SES and each aspect of social integration among Japanese older people. We used data from the Japan Gerontological Evaluation Study 2010, a self-reported survey of 23,320 functionally independent people aged 65 or older across Japan (response rate: 66.3%). Childhood SES was assessed based on respondents' subjective assessment of their SES at the age of 15. Social integration was identified as participation in community groups, social networks, being homebound, and being married. We used Poisson regression analysis with robust variance to investigate the association between childhood SES and each social integration measurement, adjusted for potential mediators; namely, adult sociodemographic characteristics, health status, health behavior (smoking), living status, and personality. Lower childhood SES had long-lasting impact on the social integration of this older Japanese cohort. In the fully adjusted model, older people with lower childhood SES were less likely to participate in community groups (Non-membership sports group or club, adjusted prevalence ratio [APR]: 1.03, 95% confidence interval [CI]: 1.00-1.06; (Non-membership hobby group, APR: 1.04; 95% CI: 1.00-1.09), almost never met friends (APR: 1.17, 95% CI: 1.11-1.24), had a smaller social network (APR: 1.13; 95% CI: 1.08-1.19), and were more likely to be homebound (APR: 1.24; 95% CI: 1.05-1.45) than those with high childhood SES. Lower childhood SES negatively affected social integration in older age. Mitigating childhood poverty might be important to increase social integration in later life, thereby improving health outcomes.